Massive intoxication with rivaroxaban, phenprocoumon, and diclofenac: A case report. Issue 44 (November 2016) - Pfeiffer, Hella; Herbst, Larissa; Schwarze, Bernd; Eckstein, Reinhold; Weisbach, Volker
Abstract: Rationale: Oral anticoagulants and painkillers, some with an additional effect on the coagulation system, are widely used and are therefore prone to abuse and (intentional) overdose. We report the case of a patient with a massive mixed anticoagulant intoxication. Patient concerns: The patient had ingested 1960 mg rivaroxaban, 31.5 mg phenprocoumon, 1425 mg diclofenac, and 21, 000 mg metamizole in suicidal intention. Diagnoses: Massive mixed anticoagulant overdose. Interventions: The patient was closely monitored. The phenprocoumon overdose was treated by the administration of vitamin K and PCC. Outcomes: Despite the massive inhibition of the coagulation system, the patient did not experience bleeding apart from a slight gross hematuria. Lessons: Despite the ingestion of a massive amount of rivaroxaban, the plasma levels were not as high as feared, due to the ceiling effect of rivaroxaban absorption. Elimination occurred according to the half-life of rivaroxaban and was not unduly prolonged by the ingested quantity.